The Maastrichtian – Danian at General Roca (Patagonia, Argentina): a reappraisal of the chronostratigraphy and biostratigraphy of a type locality - del Río, Claudia Julia (2011)
The Late Cretaceous - Early Paleogene succession exposed in the type area of the Roca Formation (General Roca, Rfo Negro Province), has been sampled in detail. Analyses of the calcareous nannofossil assemblages indicate the Late Maastrichtian - Early Danian interval (CC26-NP4 zones; MARTINI 1971), which is the first proved evidence of the Late Maastrichtian in the mentioned type area. Moreover, the "Rocanense" invertebrate fauna has been placed in a high resolution biostratigraphic scheme based on the nannofossil zones, and three assemblages have been recognized.